Pengaruh Price Discount, Online Customer Review, Dan Voucher Gratis Ongkos Kirim Terhadap Impulse Buying Pengguna Shopee Live (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Rahmadani, Diyah Ayu; Basalamah, Muhammad Ridwan; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The development of e-commerce in Indonesia is getting faster and creating more competitive competition between e-commerce. Strategies and feature innovations are often made to improve the shopping experience, one of which is live streaming shopping. Currently, live streaming shopping is the latest and most popular trend in online shopping. Shopee Live is the live streaming shopping feature that is most often used by Indonesians. The purpose of this study was to determine and analyze the effect of price discounts, online customer reviews, and free shipping vouchers on impulse buying of Shopee live users. This type of research is explanatory research using a quantitative approach. Sampling was conducted on students of the Faculty of Economics and Business, Islamic University of Malang using the Malhotra formula so that a sample of 75 respondents was obtained. This research method uses multiple linear regression analysis with SPSS 25 analysis tools. The results showed that partially price discounts, online customer reviews, and free shipping vouchers have a positive and significant effect on impulse buying. Simultaneously price discounts, online customer reviews, and free shipping vouchers have an effect on impulse buying. Keywords: Price Discount; Online Customer Review; Free Shipping Voucher; Impulse Buying